2007
DOI: 10.1007/s11010-007-9580-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of age-associated changes in mitochondrial free radical generation by rat testis

Abstract: Throughout spermatogenesis, mitochondria undergo a morphological and functional differentiation. Mitochondria are involved in the production of reactive oxygen species (ROS), considered one of the mediators of ageing. Particularly, lipid peroxidation is regarded as a major phenomenon by which ROS can impair cellular function. In the present study, we examined the production of superoxide anion, superoxide dismutase activity and the effect of Fe(2+)/ascorbate induced-lipid peroxidation on the respiratory chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 44 publications
3
22
1
Order By: Relevance
“…These observations are consistent with previous reports that ATP synthase activity decreases with advancing age in the erythrocytes of cows (Bartosz et al 1982) and the hearts of mice (Yarian et al 2005). Similarly, NADH dehydrogenase activity has also been reported to decrease with advancing age in the kidneys, livers, and testes of rats (Napoleone et al 1991;Torres-Mendoza et al 1999;Vázquez-Memije et al 2008), as well as in the livers and brains of mice (Navarro et al 2002;Navarro 2004).…”
Section: δψMsupporting
confidence: 92%
“…These observations are consistent with previous reports that ATP synthase activity decreases with advancing age in the erythrocytes of cows (Bartosz et al 1982) and the hearts of mice (Yarian et al 2005). Similarly, NADH dehydrogenase activity has also been reported to decrease with advancing age in the kidneys, livers, and testes of rats (Napoleone et al 1991;Torres-Mendoza et al 1999;Vázquez-Memije et al 2008), as well as in the livers and brains of mice (Navarro et al 2002;Navarro 2004).…”
Section: δψMsupporting
confidence: 92%
“…Vazquez-Memije et al, have reported that ROS generation and the capacity of the antioxidant system are significantly increased and decreased, respectively, in adulthood and older ages in animals on a control diet (Vazquez-Memije et al 2008). In contrast with the rat, we observed a fall in both SOD and GPx in early life in the C group.…”
Section: Discussioncontrasting
confidence: 53%
“…Our results indicated that inclusion of parsley in the diet caused an increase in the total antioxidant capacity, and these outcomes were in line with the results reported by (Nielsen et al, 1999;Rajeshwari et al, 2011a,b;Dixit et al, 2005). Reactive oxygen species concentrations increase with age, concomitantly with decreases in antioxidant levels (Weir and Robaire 2007;Vazquez-Memije et al, 2008). Malondialdehyde is a major reactive aldehyde that appears during the peroxidation of biological membrane polyunsaturated fatty acid (Vaca et al, 1988).…”
Section: Blood Compoundssupporting
confidence: 91%